Convalescence after radical orchiectomy : Detailing surgical recovery with a novel electronic patient reported outcome (ePRO) platform - Gold, Samuel A.; Jayalath, Viranda H.; Yu, Rebecca; Baky, Fady; Liso, Nicole; Williams, Brandon; Tin, Amy L.; Carlsson, Sigrid; Cracchiolo, Jennifer; Vickers, Andrew J.; Sheinfeld, Joel; Matulewicz, Richard S. (Urologic Oncology: Seminars and Original Investigations, 2025)
Purpose: To assess implementation of an electronic patient reported outcomes platform, Recovery Tracker, which characterizes short term recovery following radical orchiectomy in patients with testicular cancer. Methods: Recovery Tracker was assigned based on procedure codes to patients undergoing radical orchiectomy at our institution. Patients were surveyed daily for the 10-day postoperative period in multiple symptom domains. To assess implementation outcomes, responders of at ≥1 survey were compared to nonresponders based on demographic and disease characteristics. Responses were described to ascertain recovery across domains. Clinically significant symptoms were identified based on reporting “moderate” or greater severity, or “occasional” or higher frequency answers. Results: From 06/2021 to 10/2023, 244 patients underwent orchiectomy. 236 (97%) were assigned a survey and 206 (87%) completed ≥1 survey. American Society of Anesthesiologists score of 3-4 (a measure of health comorbidities for which higher scores indicate worse overall health) was associated with worse response rates (P = 0.014). There were no other differences in survey response rates among demographic or disease factors, including clinical stage. There were no Clavien-Dindo Grade ≥2 30-day postoperative complications and 2 (0.8%) Grade 1 complications. Regarding symptomatology, only “pain” and “limited activities due to pain” were reported to be moderate/severe among most patients early in the postoperative period. After postoperative day 5, very few patients reported moderate or severe symptoms. Conclusions: Recovery Tracker was successfully assigned to and completed by nearly all patients undergoing radical orchiectomy. Convalescence data establishes clear recovery benchmarks to provide preoperative guidance on expected symptoms and identify potential abnormal postoperative courses for rapid intervention.
Keywords: Ambulatory surgery; Patient reported outcomes; Radical orchiectomy; Symptom tracker; Testicular cancer